К проблеме изучения глагольных фразеологизмов с постпозитивной чаcтицей в современном английском языке - Каптураускене, Гедре (Kalbotyra, 1988)
Different linguistic interpretations of the English verb + adverb combinations of the type ‘give up’, ‘come off’, ‘bear out’ have been surveyed. Opinions vary depending upon different aims of research as well as unequal scope and types of the combinations included. We are of the opinion that these specific units belong to the borderland between morphology and syntax. We distinguish between the following three types of verb - adverb combinations: (1) quasi-free word combinations, e. g. come up ‘to walk upstairs’, where both constituents appear in their direct meaning, (2) semantically bound non-metaphorical phraseological units, e. g., come up ‘to approach sb.’ in which the meaning ‘direction upwards’ is not manifest in the second constituent, and (3) metaphorical phraseological units, or idioms, e. g. come up ‘to happen’. Thus, different degrees of semantic shift in the verb + adverb combinations can be observed.